HISTORY OF MATHEMATICS EDUCATION IN THE ISLAMIC COUNTRIES IN MIDDLE AGES - Abdeljaouad, Mahdi (Revista de História da Educação Matemática, 2023)
We examine some pedagogical conceptions of the Arabs/Muslims and their practical applications to the teaching of mathematics, the social function assigned to it, its place among the various disciplines taught, the nature of the institutions where mathematics was taught, the status of the students, the teachers and the institutions, the kind of curricula, subjects and textbooks and pedagogies used.